Pengujian Perangkat Lunak Diagnosa Penyakit Pada Kucing Menggunakan Metode Black-Box - Arfida, Septilia; Wibowo, Hariyanto; Sopiawati, Sri Devi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Artificial intelligence is part of the development of computer science that allows machines to function the same as humans. The use of artificial intelligence occurs in various fields, including the medical field, such as the animal hospital in Lampung City. Currently, there is only one animal hospital in Bandar Lampung. Therefore, it is very difficult for pet owners who live far from Bandar Lampung City to have their sick pets checked at a veterinary hospital. Therefore, it is deemed necessary to develop software to diagnose animal diseases, especially cat diseases, including the application of a forward chain to maximize the diagnostic process. For optimal results, our cat disease diagnosis software tests all software features using black box methods. Test results using the black box method found no errors in the diagnostic software functionality.